Objects, Models, Components, Patterns c - Vitek, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 48th International Conference on Objects, Models, Components, Patterns, held in Málaga, Spain, in June/July 2010.
Deep Meta-modelling with MetaDepth -- A Generic Meta-model-Based Approach for Specifying Framework Functionality and Usage -- Loosely-Coupled Distributed Reactive Programming in Mobile Ad Hoc Networks -- Understanding the Impact of Collection Contracts on Design -- Reasoning about Function Objects -- Welterweight Java -- Read-Only Execution for Dynamic Languages -- Optimizing Aspect-Oriented Mechanisms for Embedded Applications -- Contract-Driven Testing of JavaScript Code -- Late Binding of AspectJ Advice -- EriLex: An Embedded Domain Specific Language Generator -- Domain-Specific Program Checking -- Revisiting Parametric Types and Virtual Classes -- Moles: Tool-Assisted Environment Isolation with Closures -- Encoding Ownership Types in Java -- Visualizing Dynamic Metrics with Profiling Blueprints.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Programming Techniques; Mathematical Logic and Formal Languages; Computer Communication Networks